Challenges facing Gnöbe English Teaching Majors: An Exploration of the Quinquennial Plan for the Indigenous Peoples - Brand Fonseca, Kevin Armando (2018)
In this paper, we scrutinize the extent to which authorities and profes-sors from the Coto Campus, Brunca Extension, have orchestrated efforts to ensure the successful implementation of the Quinquennial Plan for the Indigenous Peoples in Costa Rica (QPIP). We focus on examining the experiences of three Gnöbe students enrolled in the B.A. in English Teaching offered at the Coto Campus and on analyzing the perceptions of professors and the administration regarding the implementation of the QPIP. Data collected by means of interviews, questionnaires and focus groups suggest that the objectives of the QPIP have been only partially met and that further efforts are needed to ensure its successful imple-mentation. We finish this paper by translating the students’, professors’ and administration’s concerns into concrete suggestions geared towards securing the success of the QPIP.